Tale of the Shadow King - Haack, Daniel (Haack, Daniel. Prince & knight (Series), 2021)
When a dark and mysterious Shadow King causes a fog of darkness to spread across their kingdom, the prince and the knight, now happily married, set out to find and stop him.